2023
DOI: 10.3389/fonc.2023.1110917
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of CalliSpheres drug-eluting beads for bronchial arterial chemoembolization for refractory non-small-cell lung cancer and its impact on quality of life: A multicenter prospective study

Abstract: ObjectiveThis study aimed to prospectively observe the efficacy and safety of CalliSpheres drug-eluting beads bronchial arterial chemoembolization (DEB-BACE) for refractory non-small-cell lung cancer (NSCLC).MethodsThe interventional therapy plan was as follows: 300–500 μm CalliSpheres drug-loaded microspheres were loaded with epirubicin, and then slow embolization of tumor supplying artery was performed after microcatheter superselection. Chest enhanced computed tomography and related hematological examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…In this study, minor adverse events after D-BACE plus BAIC, such as transient chest pain, nausea, vomiting, fever, and fatigue, were usually self-limiting or resolved after conservative symptomatic therapies, which is consistent with previous studies 8, 20 . Major complications such as esophageal stula, spinal cord infarction, posterior circulation cerebral infarction, and myocardial infarction due to non-target embolization were not observed in our study, and were also rare in a recent bronchial artery embolization series 5,21 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, minor adverse events after D-BACE plus BAIC, such as transient chest pain, nausea, vomiting, fever, and fatigue, were usually self-limiting or resolved after conservative symptomatic therapies, which is consistent with previous studies 8, 20 . Major complications such as esophageal stula, spinal cord infarction, posterior circulation cerebral infarction, and myocardial infarction due to non-target embolization were not observed in our study, and were also rare in a recent bronchial artery embolization series 5,21 .…”
Section: Discussionsupporting
confidence: 91%
“…However, it should be noted that squamous cancer accounted for 83.7% (36) of the patients in this prospective study, which might have in uenced the observed OS. The study reported promising e cacy with a median PFS of 7.0-11.0 months and OS of 8.0-18.4 months, as well as tolerable toxicity in patients with refractory advanced NSCLC (6, [19][20][21]. The PFS and OS rates in these studies were better than those in our study.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Hence, there may be no specific medicines suitable for treating postoperative cough. Studies have shown that cough is related to postoperative bronchial morphological changes, and the effect of medication control is often unsatisfactory 44,45 . This suggests that the current methods for treating postoperative cough have many limitations, and there is a need to explore the causes of cough after lung cancer surgery to enable the provision of patient‐targeted interventions.…”
Section: Discussionmentioning
confidence: 99%